CORTISOL AS A KEY FACTOR IN THE DEVELOPMENT OF POST-TRAUMATIC STRESS DISORDER AND THE ROLE OF MELATONIN IN THE NEUROPROTECTION OF THIS CONDITION - Byshek, M.Yu.; Berezovskyi, A.M.; Piliponova, V.V.; Sorokoumov, V.P.; Fedorchenko, O.V.; Bondar, S.A.; Terekhovskyi, A.I. (World of Medicine and Biology, 2025)
Cortisol is the most important glucocorticoid hormone, the stimulation of which is clearly organized by the hypothalamic-pituitary-adrenal axis, and the secretion itself is provided by the adrenal cortex. It plays a key role in various physiological processes. Cortisol dysfunction due to chronic stress has serious consequences for many body systems and is characterized by hyperactivity of the hypothalamic-pituitary-adrenal axis and disruption of the amygdala-cortico-hippocampal circuit - a trigger for post-traumatic stress disorder. Understanding the multifaceted mechanisms of the constant influence of this hormone is important, as it opens up prospects for mitigating the detrimental effects of traumatic disorders, for example, with the use of melatonin as part of adjuvant therapy. The purpose of the study was to analyze and summarize data from many years of research in the field of disorders arising from post-traumatic stress disorder, to deepen understanding of the importance of further directions and prospects for correcting body dysfunctions in this pathological condition. An analysis of modern publications from the scientometric databases Scopus, Web of Science, PubMed, and Google Scholar was conducted. The following keywords were searched in the PubMed database: “post-traumatic stress disorder”, “cortisol”, “hypothalamic-pituitary-adrenal axis”, “melatonin”, “acute and chronic stress”. Particular attention was paid to publications from the last 5 years to provide an analysis of modern scientific approaches. Additionally, classical studies were taken into account, which laid the foundation for further discoveries in this field. To gain a deeper understanding of the problem, articles were analyzed that included results from double-blind, randomized, placebo-controlled trials, data from meta-analyses and systematic reviews, and studies using biochemical methods to assess cortisol and melatonin levels. After collecting the literature, a critical analysis was conducted using statistical data processing tools. A comparative analysis method was used to evaluate the effectiveness of melatonin in regulating the hypothalamic-pituitary-adrenal axis and reducing symptoms of posttraumatic stress disorder. Particular attention was paid to studies examining the molecular mechanisms underlying cortisol's effects on the hippocampus and amygdala, as well as to works exploring the potential for neuroprotection with melatonin. We suggest that the use of exogenous melatonin can suppress cortisol secretion in patients with posttraumatic stress disorder and, as a result, reduce the frequency of side effects in the form of sleep dysfunction, but this issue requires further research.
Keywords: post-traumatic stress disorder; cortisol; hypothalamic-pituitary-adrenal axis; melatonin; acute and chronic stress